A frame semantic analysis of foreigner, expatriate and immigrant in Malaysian English newspapers / Yeo Huixin - Yeo, Huixin (2017)
Synonyms are a common lexical phenomenon where a pair or group of words bear semantic similarities. In a Cognitive Linguistics perspective, however, meaning goes beyond what is denoted by dictionaries with the inclusion of both linguistic and non-linguistic knowledge to fully comprehend lexical meaning. Utilizing Fillmore and Barsalou's theories on frame semantics, this study will look at how 3 synonymous nouns that denote “one who does not belong to a country”; foreigner, expatriate and immigrant are understood with the usage of Malaysian English newspapers. The study is carried out in three parts: A structural analysis, semantic analysis and finally the formation of the frames, made up of attributes to represent the background knowledge for each synonym, based on Barsalou's interpretation of the CAR frame. The study finds that although the synonyms denote “outsider”, expatriate has a more positive connotation and is associated with more positive attributes whereas foreigner and immigrant have a more negative connotation and associated with negative attributes.